PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU BERPRESTASI PADA SMP NEGERI 2 KUALUH HULU DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHT (SAW) - Sukardi Sukardi; Muhammad Bobbi Kurniawan Nasution (U-NET Jurnal Teknik Informatika, 2018)
Teachers are the most important component in Education, this Simple Additive Weight (SAW) Method can be applied as a method in designing and building decision support systems for the selection of outstanding teachers to provide alternative ranking results and determining an alternative that has the best preference value from other alternatives. Decision support system for the selection of outstanding teachers can be used to facilitate the implementation of the selection of outstanding teachers, in the process of calculating grades and determining the ranking results.